Inclusiveness and Accessibility in the Povision of Information Services in Academic Libraries in Southwest, Nigeria. - Ifeyinwa Angela, Okafor; Gbenga Omorinkoba, Oluwatosin (ADA University Library, 2024)
Digital inclusion and accessibility is an approach deployed to ensure that the web and other digital technologies are barrier-free for everyone. The essence of digital inclusiveness and accessibility is to guarantee that those with learning disabilities have equal access to information and services. It is imperative that learning disabilities should be considered during digital design process to ensure digital inclusion and accessibility for the community. This brings us to the need of inclusive designs in the design of Information and Communication Technology (ICT) System that will accommodate people with disabilities so they will not encounter barriers when accessing or interacting with the online environment. The mix methods research design was used for the study and the population included four academic libraries in Southwest Nigeria. The questionnaire and interview guide were the research instruments and results showed that 3 out of the 4 academic libraries have most of the general assistive technologies for people with disabilities. Results also shows negligence around providing assistive software and hardware for the deaf/hearing impaired and locomotive impaired in the academic libraries. It was recommended that academic libraries should give all forms of disabilities equal attention in the provision of assistive technology and information should be provided in alternative formats to enable them access needed information resources freely.
Keywords: Digital accessibility; Inclusion; Learning disabilities; ICT systems